Kolmogorov widths of the classes B^Ω_p, θ of periodic functions of many variables in the space L_q - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the Kolmogorov widths of the classes B^Ω_p, θ of periodic functions of many variables in the space L_q for 1 ≤ p, q ≤ ∞.